2002
DOI: 10.1530/eje.0.1460479
|View full text |Cite
|
Sign up to set email alerts
|

Markers of potential coeliac disease in patients with Hashimoto's thyroiditis

Abstract: Objective: Coeliac disease (CD) is associated with autoimmune thyroid disease. Gluten sensitivity represents a spectrum, with at one end cases with severe gluten-dependent enteropathy, and at the other subjects with minor signs of deranged mucosal immune response. The aim of this paper was to look for signs of minor small bowel injury and immunohistochemical markers of gluten sensitivity in a group of patients with Hashimoto's disease. Subjects and methods: Fourteen patients with Hashimoto's thyroiditis withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Also, the epithelial compartment shows signs of increased infiltration by CD3 ϩ and ␥␦ ϩ cells. Similar findings have been observed in the intestinal mucosa of patients with Hashimoto's thyroiditis (17) and could be a general feature of autoimmune disorders (18). More intriguing is the enhanced mucosal immune response to gliadin observed in biopsies from type 1 diabetic patients.…”
Section: Discussionsupporting
confidence: 82%
“…Also, the epithelial compartment shows signs of increased infiltration by CD3 ϩ and ␥␦ ϩ cells. Similar findings have been observed in the intestinal mucosa of patients with Hashimoto's thyroiditis (17) and could be a general feature of autoimmune disorders (18). More intriguing is the enhanced mucosal immune response to gliadin observed in biopsies from type 1 diabetic patients.…”
Section: Discussionsupporting
confidence: 82%
“…However, there are a limited number of studies examining the prevalence of CD in children and adolescents with autoimmune thyroid disease. In studies conducted with adults, the prevalence of CD has been reported to be 10.8-3.3% in subjects with autoimmune thyroid disease (28)(29)(30). In studies conducted with children, the prevalence of CD has been reported to be 0.3-1.2% in healthy children and 1,3-6,5% in children and adolescents with a diagnosis of autoimmune thyroiditis (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Six of these 14 patients showed an increased density of γδ + T-cell receptor-bearing intra-epithelial lymphocytes and signs of mucosal T-cell activation, both typical of CD. 94 Also among 4 of these 6 patients, HLA genotypes associated with CD (three with DRB1*04, DQB1*03 and one with DQA1*0501, DQB1*02) were described.…”
Section: Pathogenesis Of Co-existent Autoimmune Thyroid Disease and CDmentioning
confidence: 99%